Reconfigurable function block based framework for embedded application development platform - Tan, Toh Khoong. (2009)
Due to the potential of wide variety of applications needed, a quick adaptation to change and turn around the operations within the manufacturing is the only key for success. As such, the main challenge of this adaptive embedded system is to perform the change in requirements quickly and retain the flexibility in software solution. This thesis discusses about past state of adaptive embedded system development platform through literature review form general conference papers. These papers are tabulated into year of publication, type of approaches, methodologies used, research contribution, type of application and others. Base on the above, the key challenge is to find and identify the technology gap between the hardware architecture of this reconfigurable system and software as the compilation tools. Further study has been carried to identify the methodology and developmental tool to be used for addressing the change of requirements with quick response. The main focus of this dissertation is to propose a rapid developmental tool that can be rapidly developed the application in response to the changing requirement dynamically using IEC 61499 standard function block tool. It could generate XML code or Java code through customize XSL model with the help of passer to convert the high level design function block into Java, C++ or System C before deploying into the embedded system. With this proposed concept, software engineer could focus on the high level design quickly using standard library of function blocks (FB).